Religious Moderation and the Limits of Tolerance in a Plural Society in Indonesia - Bartolomeus Samho; Alfonsus Sutarno; Postinus Gulo (Parahyangan Catholic University, 2026)
This article aims to analyze religious moderation within the context of Indonesia’s plural society and to examine the limits of tolerance in religious life. This study originates from the persistence of intolerance amid constitutional guarantees of religious freedom and the growing discourse on religious moderation as a public policy agenda. This study employs a qualitative approach through a literature study and critical-normative analysis. The study integrates constitutional-legal analysis with John Rawls’ theory of reasonable pluralism, Jürgen Habermas’ theory of communicative action, and Karl Popper’s paradox of tolerance. The study analyzes various scholarly works, regulations, and theoretical concepts related to religious moderation, tolerance, and pluralism in democratic societies. The findings show that religious moderation cannot merely function as a moral appeal or an administrative instrument of the state in managing religious diversity. Religious moderation also functions as an ethical-critical framework that regulates the limits of tolerance in order to preserve justice, social cohesion, and respect for citizens’ constitutional rights within a plural society. The study also finds that tolerance without normative boundaries potentially creates space for intolerant practices within society. This study implies the need to strengthen policies and educational practices on religious moderation through more critical, dialogical, and socially just approaches. The originality of this study lies in its effort to position religious moderation not merely as a normative policy, but as an ethical-critical paradigm that bridges constitutional values, social pluralism, and lived religious realities in Indonesia.